Obesity-related ventricular remodelling is exacerbated in dilated and hypertrophic cardiomyopathy - Rayner, JJ; Abdesselam, I; d'Arcy, J; Myerson, SG; Neubauer, S; Watkins, H; Ferreira, VM; Rider, OJ (AME Publishing Company, 2020)
Background: Obesity causes significant cardiac remodelling even in health, and yet the contribution of this maladaptation in the setting of an additional cardiomyopathic process is poorly understood. Cardiovascular magnetic resonance is the gold-standard tool for assessing cardiac geometry, especially in an obese population, and hence perfectly suited to investigate this important question.